Le manager-ingénieur face aux tensions entre innovation et organisation - Stéphane Trébucq; Youssra Hdayed; Petko Atanasov (Éducation et Socialisation)
Using the case of a manager-engineer managing the implementation of a new communication infrastructure in a nuclear power plant, we show how he overcomes various contradictions within a network of actors. The objectives of improving mobility and creativity clash with the organizational imperatives of ensuring safety and security. The manager then deals with the network of actors in place, trying to convince them and facilitate their support. If the staff have difficulty anticipating new practices, the implementation is technically considered a success. However, it did not resolve the initial organizational difficulties that went beyond the scope of the project managed by the manager-engineer.